Tumor-Derived Microvesicles Modulate Antigen Cross-Processing via Reactive Oxygen Species-Mediated Alkalinization of Phagosomal Compartment in Dendritic Cells - Battisti, Federico; Napoletano, Chiara; Rahimi Koshkaki, Hassan; Belleudi, Francesca; Zizzari, Ilaria Grazia; Ruscito, Ilary; Palchetti, Sara; Bellati, Filippo; Benedetti Panici, Pierluigi; Torrisi, Maria Rosaria; Caracciolo, Giulio; Altieri, Fabio; et al. (Frontiers in Immunology, 2017)
Dendritic Cells (DCs) are the only antigen presenting cells able to prime naïve T cells and cross-prime antigen specific CD8+ T cells. Their functionality is a requirement for the induction and maintenance of long-lasting cancer immunity. Albeit intensively investigated, the in vivo mechanisms underlying efficient antigen cross-processing and presentation are not fully understood. Several evidences indicate that antigen transfer to DCs mediated by microvesicles enhances antigen immunogenicity. This mechanism is also relevant for cross-presentation of those tumor-associated glycoproteins such as MUC1 that are blocked in HLA class II compartment when internalized by DCs as soluble molecules. Here we present evidences that the internalization of tumor-derived MVs modulates antigen-processing machinery of DCs. Employing MVs derived from ovarian cancer ascites fluid and established tumor cell lines, we show that MV uptake modifies DC phagosomal microenvironment, triggering ROS accumulation and early alkalinization. Indeed, tumor MVs carry radical species and the MV uptake by DCs counteracts the chemically-mediated acidification of the phagosomal compartment. Further evidences suggest that efficacious antigen cross-priming of the MUC1 antigen carried by the tumor MVs results from the early signaling induced by MV internalization and the function of the antigen processing machinery of DCs. These results strongly support the hypothesis that tumor-derived MVs impact antigen immunogenicity by tuning the antigen processing machinery of DCs, besides being carrier of tumor antigens. Furthermore, these findings have important implications for the exploitation of MVs as antigenic cell-free immunogen for DC-based therapeutic strategies.